2023
DOI: 10.1021/acs.jcim.3c00013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hit Discovery in Virtual Screening through Absolute Protein–Ligand Binding Free-Energy Calculations

Abstract: In the hit identification stage of drug discovery, a diverse chemical space needs to be explored to identify initial hits. Contrary to empirical scoring functions, absolute protein−ligand binding free-energy perturbation (ABFEP) provides a theoretically more rigorous and accurate description of protein−ligand binding thermodynamics and could, in principle, greatly improve the hit rates in virtual screening. In this work, we describe an implementation of an accurate and reliable ABFEP method in FEP+. We validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 74 publications
5
85
0
Order By: Relevance
“…Algorithms have been proposed for the selection of Boresch restraints. ,,, At a minimum, these aim to select stable restraints based on the geometry of the complex, while more sophisticated methods aim to enhance convergence by directly (e.g., based on H-bonds) or indirectly (based on minimum total variance of the distance, angles, and dihedrals) mimicking strong receptor–ligand interactions based on a short unrestrained simulation. However, there is no obviously superior method which has been shown to guarantee selection of numerically stable restraints with optimal convergence properties.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Algorithms have been proposed for the selection of Boresch restraints. ,,, At a minimum, these aim to select stable restraints based on the geometry of the complex, while more sophisticated methods aim to enhance convergence by directly (e.g., based on H-bonds) or indirectly (based on minimum total variance of the distance, angles, and dihedrals) mimicking strong receptor–ligand interactions based on a short unrestrained simulation. However, there is no obviously superior method which has been shown to guarantee selection of numerically stable restraints with optimal convergence properties.…”
Section: Theorymentioning
confidence: 99%
“…In general, it is nontrivial to select the optimum receptor–ligand restraints. Furthermore, ABFE calculations can be challenging to converge and therefore computationally costly because the ligand is completely removed. , As a result, application studies still combine RBFE and ABFE, with ABFE applied more successfully to low molecular-weight compounds . Thus, there are barriers to the routine application of ABFE calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All simulations were performed in the μVT grand canonical ensemble, using grand canonical Monte Carlo (GCMC) with an excess chemical potential of −6.137 kcal/mol and a solvent number density of 0.03262 molecules/ Å 3 . 69 The AB-FEP 20 calculations used 68 and 108 replicas for neutral and charged ligands, respectively. The RB-FEP 14 calculations utilized 24 replicas and ran for 10 ns.…”
Section: Protein Reorganization Fep (Preorg-fep) Proteinmentioning
confidence: 99%
“…While absolute protein–ligand binding free-energy perturbation (AB-FEP) in principle can capture the apo-to-holo protein reorganization contribution to the ligand binding free energy, the long timescale associated with the conformational changes cannot be practically sampled in the relatively short AB-FEP simulations. This is why multiple studies have shown how sensitive AB-FEP results can be to different starting protein conformations. , These calculations are thus interpreted as absolute binding free energies to a specific protein conformation, and not the absolute binding free energy in vitro (Δ G exp ). The protein reorganization free energy from the apo-to-holo protein conformations is the missing piece.…”
Section: Introductionmentioning
confidence: 99%